Parental caregivers of adolescents with mental health conditions: an exploratory qualitative study of challenges and coping strategies - Cham, Choy Qing; Ibrahim, Norhayati; Kalaman, Clarisse Roswini; Ho, Meng Chuan; Visvalingam, Uma; Shahabuddin, Farah Ahmad; Abd Rahman, Fairuz Nazri; A Halim, Mohd Radzi Tarmizi; Yahya, Amira Najiha; Roslan, Samsilah; Siau, Ching Sin (BioMed Central Ltd, 2026)
Background: In Malaysia, the shift toward community-based psychiatric care has placed increased caregiving responsibilities on family members, particularly parents of adolescents with mental health conditions. Despite their central role, parental caregivers often face psychological, emotional, and social challenges, yet limited research explores their lived experiences in this context. Objective: This study aimed to explore the challenges encountered by parental caregivers of adolescents with mental health conditions and the coping strategies they employ to manage caregiving stress. Methods: An exploratory descriptive qualitative study design was employed using semi-structured interviews with 11 parental caregivers recruited through purposive sampling. Participants were mothers of adolescents receiving psychiatric treatment at public hospitals in Malaysia. Interviews were transcribed and analysed using thematic analysis. Results: Across the sample of mothers, five major themes related to caregiving challenges emerged, namely strained family relationships, stigma, time constraints, emotional distress, and low public awareness of mental health. In response, caregivers adopted diverse coping strategies, including support-seeking, emotional regulation, distraction, religious practices, and recreational activities. Conclusions: Mothers caring for adolescents with mental health conditions face significant emotional, relational, and societal challenges that affect their well-being. Nevertheless, many caregivers demonstrated resilience through the use of diverse coping strategies. These findings highlight the urgent need for structured support systems, mental health education, and caregiver-focused interventions to enhance both caregiver welfare and patient outcomes.